Massive Open Online Course in Elementary Statistics: A Tool in Empowering Data Analysis for Philippine Pre – Service Educators - Joel I. Alvarez (Asian Journal of Applied Education (AJAE), 2023)
This study aimed to determine the effectiveness of Massive Open Online Course in Elementary Statistics (MOOC – ES) in the performance of students in Statistics under the Bachelor of Secondary Education program. Using true experimental research design, this study described the performance of two groups of students in Statistics before and after a series of instruction using pre-test and post-test design and test whether there is significant difference between the post-test scores of the two groups of subjects. This study was conducted in Nueva Ecija University of Science and Technology and selected 1st Year BSE students (50) for A.Y 2020-2021 served as subjects. The subjects were statistically divided into the controlled and experimental group based on their problem-solving skills in General Mathematics. The experimental group used the MOOC while the controlled group used a series of module. Significant differences within and between groups were analyzed using T-test for dependent and independent sample respectively. After applying these statistical treatments, the following conclusions were drawn: a) There is no significant difference in the problem-solving skills of subjects under the Controlled group in the pre – test and post-test, and b) There is a significant difference in the problem-solving skills of subjects under the Experimental group in the pre – test and post-test. Also, There is a significant difference in the problem-solving skills of the students between the two groups after instruction. Furthermore, a specific and concrete format and guidelines of MOOCs to be developed by the College was crafted.